Hes1 expression is reduced in Tbx1 null cells and is required for the development of structures affected in 22q11 deletion syndrome. - van Bueren, K; Papangeli, I; Rochais, F; Pearce, K; Roberts, C; Calmont, A; Szumska, D; Kelly, R; Bhattacharya, S; Scambler, P (2010)
22q11 deletion syndrome (22q11DS) is characterised by aberrant development of the pharyngeal apparatus and the heart with haploinsufficiency of the transcription factor TBX1 being considered the major underlying cause of the disease. Tbx1 mutations in mouse phenocopy the disorder. In order to identify the transcriptional dysregulation in Tbx1-expressing lineages we optimised fluorescent-activated cell sorting of beta-galactosidase expressing cells (FACS-Gal) to compare the expression profile of Df1/Tbx1(lacZ) (effectively Tbx1 null) and Tbx1 heterozygous cells isolated from mouse embryos. Hes1, a major effector of Notch signalling, was identified as downregulated in Tbx1(-)(/)(-) mutants. Hes1 mutant mice exhibited a partially penetrant range of 22q11DS-like defects including pharyngeal arch artery (PAA), outflow tract, craniofacial and thymic abnormalities. Similar to Tbx1 mice, conditional mutagenesis revealed that Hes1 expression in embryonic pharyngeal ectoderm contributes to thymus and pharyngeal arch artery development. These results suggest that Hes1 acts downstream of Tbx1 in the morphogenesis of pharyngeal-derived structures.